Comparison Of Neonatal Morbidity and Mortality Among Late Preterm and Term Neonates at Neonatal Intensive Care Unit in Gujarat - Rohit Modi; Bhavesh Modi; Jaiminkumar Patel (Medsci Publications, 2015)
Background: Late preterm infants are physiologically less mature and have limited compensatory responses to the extra-uterine envi- ronment, compared with term infants. Although late preterm infants are the largest subgroup of preterm infants, there has been little re- search on this group until recently. Aims: The present study is an attempt to obtain actual data on pat- tern of early neonatal morbidities and mortality among late preterm infant. Material and Methods: This hospital based retrospective study was carried out by enrolling live newborns admitted during January 2014 to December 2014 in the neonatal intensive care unit at Civil Hospit- al, Gandhinagar, Gujarat. With ethical permission from Institutional Ethical Committee and administrative permission from medical su- perintendent files of the neonates were retrospectively reviewed. Results: Mean weight in term neonates is more (3.14±0.48) than late preterm neonates (2.35±0.43). Chance of any morbidity is almost 3 times higher in late preterm compared to term neonates. Proportional death rate is more than double in late preterm neonates (13.79%) compared to term neonates (6.25%). Conclusion: Late preterm neonates are at higher risk of different morbidities and mortalities so they required extra care and special attention for prevention of any adverse effect.